The Concept of Motherhood in a Modern Fiction Text (Mother's Time by G. Sosiashvili) - Gogoladze, Tamar; Barbakadze, Ketevan ("Intercultural Dialogues" Transactions, 2023)
The concept of motherhood was forming or changing according to cultures, traditions or religious and moral laws in the history of different people and, accordingly, in folklore or artistic texts. Over time, it has been developing from matriarchal-patriarchal to alienation with a dynamic drive. In the 21st century, this is reflected in the artistic text as well. The article presents it on the example of the writer Giorgi Sosiashvili's story "Mother's Time". The story told by the author of the prose text also includes the elements of the story of three people, in the background of which the vicissitudes of motherhood towards the aged mother of the child are formed. The "sunny-shady" and the "two-eyed" relationship of Ilia is developed more from the point of view of the child than from the mother's point of view, which is more or less alienated in accordance with the change of environmental conditions and the tradition brought by the new times. Through the eyes of the author, the world is seen with amazing, deep psychologism, in which filial love is associated with its fragrance, so strangely it stirs it. Approaching the time of death reinforces the need to spend the time of life as close as possible to the mother. The variety of characters seems to be different, but they unite the sunny and shadowy aspects of love for the mother. The article shows the development of the concept of motherhood by witnessing his mother's death, presenting a dreamlike narrative of being admitted to an asylum. The father also appears in the story in the background of the dialogue between the brothers, but is presented as a retrospect of his loving family upbringing. The language of the author, Giorgi Sosiashvili, is still calm here, with exceptionally expressive phraseology, which acquires the power of psychological loading. The face of the characters is given more compactly, as if nothing more is needed to say. The main story revolves around the mother. This fictional text of the 1920s of the 21st century is valuable as a true concept of motherhood that must exist.